The impact of immigration on the local labor market outcomes of blue collar workers: panel data evidence - Ortega, Javier; Verdugo, Gregory (London, 2015)
"Using a large administrative French panel data set for 1976-2007, we examine how low- educated immigration affects the wages, employment, occupations and locations of blue-collar native workers. The natives in the sample are initially in occupations heterogeneous in the presence of immigrants, which might reflect a different degree of competition with low-educated immigrants. We first show that larger immigration inflows into locations are accompanied by larger outflows of negatively selected natives from these locations. At the same time, larger immigrant inflows into occupations come with larger outflows of positively selected natives towards occupations with less routine tasks. While we find no negative impact on employment, there is substantial evidence that immigration lowers the median annual wages of natives. The estimated negative effects are also much larger in cross-section than in estimates controlling for composition effect, which is consistent with the idea that endogenous changes in occupation and location attenuate the impact of immigration on natives’ wages. We also find much larger wage decreases for workers initially in non-tradable sectors and more particularly in the construction sector, which are much less likely to upgrade their occupation or change location in response to immigration inflows."